INFLUENCE OF GLASS POWDER ON THE PROPERTIES OF CONCRETE - KUMAR, B.NAGA NIRANJAN; KUMAR, DR.M.ASHOK (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
Concrete is a construction material composed of cement, aggregates (fine & course) water and admixture. Today many researches are on going into the use of Portland cement replacement, using many waste materials like fly ash, rice husk, furnace slag, marble powder and silica flume.The main objective of present study to use of glass powder to increase the compressive strength of concrete. Glass powder is used as a binder with partial replacement of cement which takes some part of reaction at the time of hydration; also it is act as a filler material. Present days most of the ways glasses have been dumped in to land fill site. When waste glasses are re-used in making concrete production, the production cost of concrete will go down.In this report we are going to discuss the strength effect of replacement of cement by glass powder, the cement is replaced at 10%, 20% 30%. The compressive strength of concrete cubes is tested for 3, 7, 28 days were found. The highest replacement level is 20% by WGP (waste glass powder). The performance of design mix and properties of materials are good.